Reflective Practice in ESL Teacher Development Groups - Farrell, T. author. aut Link
VII, 162 p.
Keywords: Reflective Practice in ESL Teacher Development Groups discusses the concept of reflective practice in ESL teachers using data from a 3-year collaborative partnership in which three ESL teachers in Canada explored their professional development through reflective practice.